A negociação de sentidos sobre participação: um estudo dos processos dialógicos do orçamento participativo de Ipatinga-MG, pelo viés da cidadania - Borba, Gustavo Lopes (2005)
BORBA, Gustavo Lopes. A negociação de sentidos sobre participação: Um estudo dos processos dialógicos do Orçamento Participativo de Ipatinga-MG, pelo viés da Cidadania. Dissertação de mestrado em psicologia social. São Paulo: PUC-SP, 2005. The work sought to understand how happens negotiation of senses about participation in the experience of the participatory budget (PB) implanted in the city of Ipatinga-MG, that exists for 16 years. By new ways of public management allowed by the re-democratization, those experiences of deliberative democracy have spread in Brazil and in the world. While the social scientists are interested in the political aspects of the process, my interest as a social psychologist concerns on how those new processes led to changes in the way that people will understand their own world. Working with the referential of Hacking (2001) for work with the analysis of matrices that embodies both ideas and human constructs, the material elements that compose the experience of the PB were sought and considered while elements that are part of the social relations. Hacking talks from the constructionist movement in social psychology aiming an approach about senses, nets of socialities and materialities. The senses also they can be found in documents of public domain (SPINK, 2000), that are rounding materialities in the public environment, what permits to consider the positionings of the diverse agents in the field. The research s results let us to find out that the negotiations occur with a difference between the population and the city hall as regards the vision of the process of the PB. The population is more prone to the possibility of true deliberation, depositing in the PB the expectation of the resolution of the problems of the community through the dialogue. The city hall sees the PB as a process that makes the citizen more closer of the city hall, so that they can be more aware about the management and the administrative difficulties. Besides, the city hall seems to consider the PB as a process that allows the improvement of the quality of life of the population. The most important aspects for the negotiation of senses were: of the part of the city hall, the mass communication resources use, mainly newspapers and magazines, and the use of the structure of the city hall for receive the representatives of the population unhappy or, on the contrary one, for award the allied. Of the part of the population, to traditional presence of the associations of inhabitants were shown like an aspect that itself remains based in the informal personal relations, more than about relations with formal character. An example of that is the little relevance of the counselors of the PB to the population, being more important the own inhabitants associations representatives.